Alternative strategies for dairy development - Brumby, P.J. (International Service for National Agricultural Research, 1983)
Discusses the role of livestock in the agricultural Development of African countries, using the "Anand" model developed in India to demonstrate successful dairy Development strategies based on a small producer's cooperative.